2020
DOI: 10.1002/ccr3.3568
|View full text |Cite
|
Sign up to set email alerts
|

A rare cause of persistent hyperparathyroidism

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…[3] Therefore, other imaging methods are used in the research protocol to locate parathyroid adenomas more precisely. [4] For instance, a case presented by Iconaru et al [5] reported that 18 F-fluorocholine (FCH) positron emission tomography/computed tomography (PET-CT) was useful in localizing an ectopic parathyroid adenoma in the retropharyngeal space, which is a very unusual and elusive location even in ectopic cases.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Therefore, other imaging methods are used in the research protocol to locate parathyroid adenomas more precisely. [4] For instance, a case presented by Iconaru et al [5] reported that 18 F-fluorocholine (FCH) positron emission tomography/computed tomography (PET-CT) was useful in localizing an ectopic parathyroid adenoma in the retropharyngeal space, which is a very unusual and elusive location even in ectopic cases.…”
Section: Introductionmentioning
confidence: 99%